Pendekatan Sinergis Antara Ajaran Islam Dengan Analisis Data Kategorik Berdasarkan Q.S. Al-Hujurat Ayat 13 - Muna, Faiqotul; Lailiyah, Zuhairina Desiyatul (Kaunia: Integration and Interconnection Islam and Science Journal, 2024)
According to this research, understanding and addressing complex social issues is crucial. This article emphasises the differences between religion and science and how they affect how we understand the social world, particularly Muslim communities with different views on Western civilisation. The thirteenth verse of Surah Al-Hujurat in the Qur'an is analysed along with categorical data analysis techniques to investigate the issue of prejudice in society. This paper aims to enhance our understanding of the moral principles contained in religious teachings and how to overcome prejudice in society through the incorporation of these principles. The research method combines the interpretation of Qur'anic verses with statistical concepts, resulting in a deeper understanding of the issues. In conclusion, this article demonstrates the importance of interdisciplinary integration in understanding and addressing complex social issues.